Assessing the efficacy of coral restoration along Florida’s coral reef under the chronic persistence of stony coral tissue loss disease - William C. Sharp; Kristene T. Parsons; Erinn M. Muller; Amanda Bourque; David S. Gilliam; Diego Lirman; Colin P. Shea; Joshua D. Voss; John H. Hunt (Frontiers in Marine Science, 2026)
Stony coral tissue loss disease (SCTLD) has caused unprecedented coral mortality across Florida’s Coral Reef (FCR) since 2014, raising concerns about whether coral restoration can succeed under chronic disease conditions and whether outplanting activities may increase disease transmission risk. As the disease transitioned from epizootic outbreak to enzootic persistence, we conducted a large-scale experimental outplanting to assess coral restoration efficacy under chronic SCTLD persistence and to evaluate the relative importance of SCTLD versus non-disease drivers of restoration outcomes. From May 2021 through April 2023, we outplanted 1,165 colonies of three SCTLD-susceptible species ( Montastraea cavernosa, Orbicella faveolata , and Pseudodiploria clivosa ) sourced from land-based facilities and in-water nurseries across six regions spanning FCR and monitored survival and disease incidence. Concurrent surveys of natural coral communities assessed whether outplanting activities affected local SCTLD prevalence. Probabilities of infection per monitoring interval remained <1-2% across all species, regions, and propagation sources throughout the monitoring period. Importantly, outplanting activities did not increase SCTLD prevalence in neighboring natural coral communities. In contrast to the low and relatively uniform disease incidence, variation in coral survival was strongly structured by ecological and operational factors. The overall coral colony survival rate at the end of the study was 77.3% but was influenced by reef stratum (inshore vs. offshore reefs), geographic region, and colony source. M. cavernosa and P. clivosa exhibited higher survival at inshore sites compared to offshore sites, whereas O. faveolata showed no consistent reef stratum effect on survival. Across FCR, survival varied spatially between regions independent of latitude, suggesting local environmental drivers. Colony source effects varied by species. M. cavernosa and P. clivosa from land-based facilities exhibited significantly lower survival than colonies from in-water nurseries, whereas O. faveolata showed no significant differences between propagation sources. Our results indicate that under SCTLD-enzootic conditions, restoration outcomes are shaped more strongly by habitat suitability, geographic context, and propagation-related factors than by SCTLD itself. These findings suggest that coral restoration can proceed within SCTLD-enzootic zones without increasing disease risk to neighboring coral communities or substantially elevating SCTLD-related mortality of outplanted colonies.

Role of freshwater availability and terrestrial land‐cover change in the distribution of a declining, terrestrial, insectivorous bird - Catrin F. Eden; Simon Gillings; Richard K. Broughton; Bart Donato; Chris M. Hewson; Stuart P. Sharp (Conservation Biology, 2026)
Insectivorous, Afro‐Palearctic migrant birds provide cross‐border ecosystem services, but many are declining rapidly. The complex life cycle of migrant birds makes their conservation difficult, but understanding where they spend time during the breeding season can help indicate where those actions will be most effective. We used the spotted flycatcher ( Muscicapa striata ), a declining, Afro‐Palearctic, migratory insectivore and habitat generalist, as a model to examine how river density and land‐cover change were associated with loss and colonization during the breeding season of 2 × 2‐km national atlas survey areas from 1990 to 2010. Greater river density was associated with a lower probability of loss (odds ratio [OR] 0.8) between survey periods and a higher probability of colonization (OR 1.25). Loss was associated with increases in urban land cover (OR 1.17), and, unexpectedly, colonization was negatively associated with increases in woodland (OR 0.91) and standing freshwater (OR 0.94). Our results suggest that habitat creation is unlikely to provide sufficient benefits for some insectivorous birds within the time needed for population recovery. Thus, efforts should focus on the protection and improvement of established habitats. River density was strongly associated with the persistence of the spotted flycatcher, and this finding highlights that understanding the benefits of freshwater habitat for terrestrial species should be a priority for conservation management.

Impact of climate change on freshwater macronutrients and agricultural yields across Britain - Nathan Missault; Victoria A. Bell; David M. Cooper; Ryan T. Sharp; Andrew P. Whitmore; Alice E. Milne; Helen N. Davies (Journal of Environmental Management, 2026)

Nitric oxide (NO) and nitrogen dioxide (NO2): A state-of-knowledge review of their roles in, and consequences for, vegetation and ecosystems - Michael P. Perring; Laurence Jones; Katrina Sharps; Felicity Hayes (Atmospheric Environment, 2026)

Rethinking land-use Strategies: A multi-objective analysis of combined sparing and sharing approaches applied across great britain - Imane El Fartassi; Ryan T. Sharp; Victoria A. Bell; Andrew P. Whitmore; Helen Metcalfe; Nathan Missault; John Redhead; David M. Cooper; Jonathan Storkey; Helen Davies; Theo Jackson; Kevin Coleman; et al. (Journal of Environmental Management, 2026)

Urban surface water flows contribute more PFAS to marine environments than treated wastewater - Phoebe Lewis; Erica Odell; Christopher P. Johnstone; Timothy Chaston; Daniel MacMahon; Tanya Paige; Simon Sharp; Mark Patrick Taylor; Vincent Pettigrove; Minna Saaristo (Environmental Research, 2025)

Cross-system transfer of fatty acids from aquatic insects supports terrestrial insectivore condition and reproductive success - Catrin F. Eden; Richard K. Broughton; Bart Donato; Chris M. Hewson; Caroline Isaksson; Stuart P. Sharp (Oecologia, 2025)
Cross-system fluxes of aquatic insects rich in omega-3 long-chain polyunsaturated fatty acids (ω-3 LC-PUFAs), specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), may subsidise insectivorous vertebrates that are suffering due to terrestrial insect declines. The benefits of high ω-3 LC-PUFA diets, such as improved growth and immunocompetence, have previously been demonstrated for riparian insectivores. Understanding the potential for aquatic insects to benefit a range of species is necessary for informing land management practices. Using the spotted flycatcher ( Muscicapa striata ), a habitat-generalist, insectivorous bird as a model, we tested how blood plasma ω-3 LC-PUFA concentrations and the ratio of ω-6:ω-3 fatty acids were related to the body condition of 14 adults and 84 chicks in the wild. We measured how variation in ω-3 LC-PUFAs and ω-6:ω-3 was related to river proximity, to test whether they were related to aquatic insect availability. We assessed how these relationships may extend beyond the individual level by monitoring flying insect availability throughout two breeding seasons and testing its ability to predict reproductive success. EPA was positively correlated with body condition in chicks and adults and declined with distance from a river. Conversely, ω-6:ω-3 was negatively correlated with body condition and increased with distance from a river. Breeding success was positively correlated with aquatic insect availability, suggesting that access to a high ω-3 LC-PUFA diet has the potential to mitigate declines in generalist insectivores. Our results highlight how the maintenance or creation of high-quality freshwater habitats may be promoted in a conservation context for non-riparian species.

Assimilatory processes dominate diel inorganic nitrogen cycling in a shallow open-water constructed wetland - Richard L. Smith; Ariel P. Reed; Deborah A. Repert; Craig R. Tobias; Jonathan O. Sharp (Science of The Total Environment, 2025)

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

A content analysis of parents’ reflections on pathogenic and uncertain pediatric oncology germline sequencing results - Katianne M. Howard Sharp; Mary Egan Clark; Niki Jurbergs; Annastasia Ouma; Lynn Harrison; Leslie Taylor; Kayla Hamilton; Rose B. McGee; Regina Nuccio; Stacy Hines-Dowell; Jami S. Gattuso; Michelle Pritchard; et al. (Familial Cancer, 2024)

Implications and impacts of aligning regional agriculture with a healthy diet - Ryan T. Sharp; Angelina Sanderson Bellamy; Adrian Clear; Samantha Mitchell Finnigan; Ella Furness; Elliot Meador; Helen Metcalfe; Susanna Mills; Kevin Coleman; Andrew P. Whitmore; Alice E. Milne (Journal of Cleaner Production, 2024)

Public perceptions of per- and polyfluoroalkyl substances (PFAS): Psycho-demographic characteristics differentiating PFAS knowledge and concern - Joya A. Kemper; Emma Sharp; Shan Yi; Erin M. Leitao; Lokesh P. Padhye; Melanie Kah; Jack L.-Y. Chen; Kapish Gobindlal (Journal of Cleaner Production, 2024)

Sustained ICP Elevation Is a Driver of Spatial Memory Deficits After Intraventricular Hemorrhage and Leads to Activation of Distinct Microglial Signaling Pathways - Chloe H. Puglisi; Bradley P. Ander; Catherine Peterson; Janet A. Keiter; Heather Hull; Cameron W. Hawk; Venina S. Kalistratova; Ali Izadi; Gene G. Gurkoff; Frank R. Sharp; Ben Waldau (Translational Stroke Research, 2023)

What's the crux? Falcon nesting closures and rock climbing constraints at Harpers Ferry National Historical Park - Michala L. Hendrick; Chris A.B. Zajchowski; Jessica P. Fefer; Ryan L. Sharp; Chandler Berry; James N. Maples; Eddie L. Hill (Journal of Outdoor Recreation and Tourism, 2023)

The blowfly Chrysomya latifrons inhabits fragmented rainforests, but shows no population structure - Nathan J. Butterworth; James F. Wallman; Nikolas P. Johnston; Blake M. Dawson; Joshua Sharp-Heward; Angela McGaughran (Oecologia, 2023)
Climate change and deforestation are causing rainforests to become increasingly fragmented, placing them at heightened risk of biodiversity loss. Invertebrates constitute the greatest proportion of this biodiversity, yet we lack basic knowledge of their population structure and ecology. There is a compelling need to develop our understanding of the population dynamics of a wide range of rainforest invertebrates so that we can begin to understand how rainforest fragments are connected, and how they will cope with future habitat fragmentation and climate change. Blowflies are an ideal candidate for such research because they are widespread, abundant, and can be easily collected within rainforests. We genotyped 188 blowflies ( Chrysomya latifrons ) from 15 isolated rainforests and found high levels of gene flow, a lack of genetic structure between rainforests, and low genetic diversity – suggesting the presence of a single large genetically depauperate population. This highlights that: (1) the blowfly Ch. latifrons inhabits a ~ 1000 km stretch of Australian rainforests, where it plays an important role as a nutrient recycler; (2) strongly dispersing flies can migrate between and connect isolated rainforests, likely carrying pollen, parasites, phoronts, and pathogens along with them; and (3) widely dispersing and abundant insects can nevertheless be genetically depauperate. There is an urgent need to better understand the relationships between habitat fragmentation, genetic diversity, and adaptive potential–especially for poorly dispersing rainforest-restricted insects, as many of these may be particularly fragmented and at highest risk of local extinction.

Assessing variability in marine traffic exposure between baleen whale species off the Galician Coast, Spain - Rhian Bland; Séverine Methion; Stuart P. Sharp; Bruno Díaz López (Marine Pollution Bulletin, 2023)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Are mutations usually deleterious? A perspective on the fitness effects of mutation accumulation - Kevin Bao; Robert H. Melde; Nathaniel P. Sharp (Evolutionary Ecology, 2022)

Use of multiple endpoints to assess the impact of captivity on gut flora diversity in Long Island Sound Fundulus heteroclitus - Joseph P. Battaglia; Christian M. Kearney; Kirsten Guerette; Jordan Corbishley; Emily Sanchez; Brennah Kent; Hanna Storie; Emma Sharp; Shane Martin; Matthew Saberito; Jonathan D. Blake; Richard S. Feinn; et al. (Environmental Biology of Fishes, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Correction to: Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)

Molecular Correlates of Hemorrhage and Edema Volumes Following Human Intracerebral Hemorrhage Implicate Inflammation, Autophagy, mRNA Splicing, and T Cell Receptor Signaling - Marc Durocher; Bodie Knepp; Alan Yee; Glen Jickling; Fernando Rodriguez; Kwan Ng; Xinhua Zhan; Farah Hamade; Eva Ferino; Hajar Amini; Paulina Carmona-Mora; Heather Hull; et al. (Translational Stroke Research, 2021)
Intracerebral hemorrhage (ICH) and perihematomal edema (PHE) volumes are major determinants of ICH outcomes as is the immune system which plays a significant role in damage and repair. Thus, we performed whole-transcriptome analyses of 18 ICH patients to delineate peripheral blood genes and networks associated with ICH volume, absolute perihematomal edema (aPHE) volume, and relative PHE (aPHE/ICH; rPHE). We found 440, 266, and 391 genes correlated with ICH and aPHE volumes and rPHE, respectively ( p < 0.005, partial-correlation > |0.6|). These mainly represented inflammatory pathways including NF-κB, TREM1, and Neuroinflammation Signaling—most activated with larger volumes. Weighted Gene Co-Expression Network Analysis identified seven modules significantly correlated with these measures ( p < 0.05). Most modules were enriched in neutrophil, monocyte, erythroblast, and/or T cell-specific genes. Autophagy, apoptosis, HIF-1α, inflammatory and neuroinflammatory response (including Toll-like receptors), cell adhesion (including MMP9), platelet activation, T cell receptor signaling, and mRNA splicing were represented in these modules (FDR p < 0.05). Module hub genes, potential master regulators, were enriched in neutrophil-specific genes in three modules. Hub genes included NCF2, NCF4, STX3, and CSF3R, and involved immune response, autophagy, and neutrophil chemotaxis. One module that correlated negatively with ICH volume correlated positively with rPHE. Its genes and hubs were enriched in T cell-specific genes including hubs LCK and ITK, Src family tyrosine kinases whose modulation improved outcomes and reduced BBB dysfunction following experimental ICH. This study uncovers molecular underpinnings associated with ICH and PHE volumes and pathophysiology in human ICH, where knowledge is scarce. The identified pathways and hub genes may represent novel therapeutic targets.

Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)
Purpose Heat stress exacerbates post-exercise hypotension (PEH) and cardiovascular disturbances from elevated body temperature may contribute to exertion-related incapacity. Mast cell degranulation and muscle mass are possible modifiers, though these hypotheses lack practical evidence. This study had three aims: (1) to characterise pre–post-responses in histamine and mast cell tryptase (MCT), (2) to investigate relationships between whole body muscle mass (WBMM) and changes in blood pressure post-marathon, (3) to identify any differences in incapacitated runners. Methods 24 recreational runners were recruited and successfully completed the 2019 Brighton Marathon (COMPLETION). WBMM was measured at baseline. A further eight participants were recruited from incapacitated runners (COLLAPSE). Histamine, MCT, blood pressure, heart rate, body temperature and echocardiographic measures were taken before and after exercise (COMPLETION) and upon incapacitation (COLLAPSE). Results In completion, MCT increased by nearly 50% from baseline ( p = 0.0049), whereas histamine and body temperature did not vary ( p > 0.946). Systolic (SBP), diastolic (DBP) and mean (MAP) arterial blood pressures and systemic vascular resistance (SVR) declined ( p < 0.019). WBMM negatively correlated with $$Δ $$ Δ SBP ( r = − 0.43, p = 0.046). For collapse versus completion, there were significant elevations in MCT (1.77 ± 0.25 μg/L vs 1.18 ± 0.43 μg/L, p = 0.001) and body temperature (39.8 ± 1.3 °C vs 36.2 ± 0.8 °C, p < 0.0001) with a non-significant rise in histamine (9.6 ± 17.9 μg/L vs 13.7 ± 33.9 μg/L, p = 0.107) and significantly lower MAP, DBP and SVR ( p < 0.033). Conclusion These data support the hypothesis that mast cell degranulation is a vasodilatory mechanism underlying PEH and exercise associated collapse. The magnitude of PEH is inversely proportional to the muscle mass and enhanced by concomitant body heating.

Insulin regulates human mammosphere development and function - Ashalyn P. Watt; Christophe Lefevre; Cynthia S. Wong; Kevin R. Nicholas; Julie A. Sharp (Cell and Tissue Research, 2021)

HDAC9 Polymorphism Alters Blood Gene Expression in Patients with Large Vessel Atherosclerotic Stroke - Natasha Shroff; Bradley P. Ander; Xinhua Zhan; Boryana Stamova; DaZhi Liu; Heather Hull; Farah R. Hamade; Cheryl Dykstra-Aiello; Kwan Ng; Frank R. Sharp; Glen C. Jickling (Translational Stroke Research, 2019)

The structure and context of male and female song in White-throated Dippers - Lucy Magoolagan; Peter J. Mawby; Flora A. Whitehead; Stuart P. Sharp (Journal of Ornithology, 2019)

Fine‐scale genetic structure and helping decisions in a cooperatively breeding bird - Amy E. Leedale; Stuart P. Sharp; Michelle Simeoni; Elva J. H. Robinson; Ben J. Hatchwell (Molecular Ecology, 2018)
In animal societies, characteristic demographic and dispersal patterns may lead to genetic structuring of populations, generating the potential for kin selection to operate. However, even in genetically structured populations, social interactions may still require kin discrimination for cooperative behaviour to be directed towards relatives. Here, we use molecular genetics and long‐term field data to investigate genetic structure in an adult population of long‐tailed tits Aegithalos caudatus , a cooperative breeder in which helping occurs within extended kin networks, and relate this to patterns of helping with respect to kinship. Spatial autocorrelation analyses reveal fine‐scale genetic structure within our population, such that related adults of either sex are spatially clustered following natal dispersal, with relatedness among nearby males higher than that among nearby females, as predicted by observations of male‐biased philopatry. This kin structure creates opportunities for failed breeders to gain indirect fitness benefits via redirected helping, but crucially, most close neighbours of failed breeders are unrelated and help is directed towards relatives more often than expected by indiscriminate helping. These findings are consistent with the effective kin discrimination mechanism known to exist in long‐tailed tits and support models identifying kin selection as the driver of cooperation.

The Regulation of Monoamine Oxidase A Gene Expression by Distinct Variable Number Tandem Repeats - Maurizio Manca; Veridiana Pessoa; Ana Illera Lopez; Patrick T. Harrison; Fabio Miyajima; Helen Sharp; Andrew Pickles; Jonathan Hill; Chris Murgatroyd; Vivien J. Bubb; John P. Quinn (Journal of Molecular Neuroscience, 2018)

Phosphodiesterase 4 inhibition affects both the direct and indirect pathway: an electrophysiological study examining the tri-phasic response in the substantia nigra pars reticulata - P. R. A. Heckman; J. V. Schweimer; T. Sharp; J. Prickaerts; A. Blokland (Brain Structure and Function, 2018)

In vitro Approaches to Support Bioequivalence and Substitutability of Generic Proton Pump Inhibitors via Nasogastric Tube Administration - Ping Ren; Minglei Cui; Om Anand; Li Xia; Zhuojun J. Zhao; Dajun Sun; Trueman Sharp; Dale P. Conner; John Peters; Wenlei Jiang; Ethan Stier; Xiaojian Jiang (The AAPS Journal, 2017)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Critical Review on the Public Health Impact of Norovirus Contamination in Shellfish and the Environment: A UK Perspective - Francis Hassard; Jasmine H. Sharp; Helen Taft; Lewis LeVay; John P. Harris; James E. McDonald; Karen Tuson; James Wilson; David L. Jones; Shelagh K. Malham (Food and Environmental Virology, 2017)

Temporal and spectral audiotactile interactions in musicians - Simon P. Landry; Andréanne Sharp; Sara Pagé; François Champoux (Experimental Brain Research, 2017)

Molecular variability and phylogenetic relationships of guava (Psidium guajava L.) cultivars using inter-primer binding site (iPBS) and microsatellite (SSR) markers - A. Mehmood; S. Luo; N. M. Ahmad; C. Dong; T. Mahmood; Y. Sajjad; M. J. Jaskani; P. Sharp (Genetic Resources and Crop Evolution, 2016)

Fairway patch - a serious emerging disease of couch (syn. bermudagrass) [Cynodon dactylon] and kikuyu (Pennisetum clandestinum) turf in Australia caused by Phialocephala bamuru P.T.W. Wong & C. Dong sp. nov. - P. T. W. Wong; C. Dong; P. M. Martin; P. J. Sharp (Australasian Plant Pathology, 2015)

Variability in summer anticyclonic circulation over the Canadian Arctic Archipelago and west Greenland in the late 20th/early 21st centuries and its effect on glacier mass balance - P. Bezeau; M. Sharp; G. Gascon (International Journal of Climatology, 2015)
More frequent summer anticyclonic circulation over the Canadian Arctic Archipelago ( CAA ) between 2007 and 2012 caused more intense and sustained melt of ice caps and glaciers and increased rates of mass loss. To determine the frequency of the occurrence of anticyclonic circulation over the CAA and western Greenland, a self‐organizing map ( SOM ) was used to classify daily 500 hPa geopotential height (GPH) anomalies calculated from National Centers for Environmental Prediction and the National Center for Atmospheric Research ( NCEP / NCAR ) Reanalysis 1 (1948–2012) and five Coupled Model Intercomparison Project Phase 5 ( CMIP5 ) models (1950–2025). While the NCEP / NCAR reanalysis indicates that significant summer warming over the CAA is linked to a doubling in the frequency of anticyclonic circulation over the region since 2007, the CMIP5 models were not capable of reproducing the magnitude of the trend in the frequency of anticyclonic circulation over the CAA and western Greenland found in NCEP / NCAR . The variability of the frequency of positive anomalies in summer 500 hPa GPH was found to be related to variability of Arctic sea ice volume/thickness in April, May and June (1979–2012) and to poleward eddy heat flux in June (1979–2012).

Dominance, not kinship, determines individual position within the communal roosts of a cooperatively breeding bird - Clare J. Napper; Stuart P. Sharp; Andrew McGowan; Michelle Simeoni; Ben J. Hatchwell (Behavioral Ecology and Sociobiology, 2013)

Soil–plant N processes in a High Arctic ecosystem, NW Greenland are altered by long‐term experimental warming and higher rainfall - Sean M. Schaeffer; Elizabeth Sharp; Joshua P. Schimel; Jeffery M. Welker (Global Change Biology, 2013)
Rapid temperature and precipitation changes in High Arctic tundra ecosystems are altering the biogeochemical cycles of carbon (C) and nitrogen (N), but in ways that are difficult to predict. The challenge grows from the uncertainty of N cycle responses and the extent to which shifts in soil N are coupled with the C cycle and productivity of tundra systems. We used a long‐term (since 2003) experiment of summer warming and supplemental summer water additions to a High Arctic ecosystem in NW Greenland, and applied a combination of discrete sampling and in situ soil core incubations to measure C and N pools and seasonal microbial processes that might control plant‐available N. We hypothesized that elevated temperature and increased precipitation would stimulate microbial activity and net inorganic N mineralization, thereby increasing plant N‐availability through the growing season. While we did find increased N mineralization rates under both global change scenarios, water addition also significantly increased net nitrification rates, loss of NO 3 − ‐N via leaching, and lowered rates of labile organic N production. We also expected the chronic warming and watering would lead to long‐term changes in soil N‐cycling that would be reflected in soil δ 15 N values. We found that soil δ 15 N decreased under the different climate change scenarios. Our results suggest that temperature accelerates biological processes and existing C and N transformations, but moisture increases soil hydraulic connectivity and so alters the pathways, and changes the fate of the products of C and N transformations. In addition, our findings indicate that warmer, wetter High Arctic tundra will be cycling N and C in ways that may transform these landscapes in part leading to greater C sequestration, but simultaneously, N losses from the upper soil profile that may be transported to depth dissolved in water and or transported off site in lateral flow.

Assessing the sensitivity of habitats to fishing: from seabed maps to sensitivity maps a - N. C. Eno; C. L. J. Frid; K. Hall; K. Ramsay; R. A. M. Sharp; D. P. Brazier; S. Hearn; K. M. Dernie; K. A. Robinson; O. A. L. Paramor; L. A. Robinson (Journal of Fish Biology, 2013)
In the Welsh part of the Irish Sea, a method was developed for assessing the sensitivity of different seabed habitats to existing fishing activities, across a range of potential fishing intensities. The resistance of 31 habitats and their associated biological assemblage to damage by 14 categories of fishing activity were assessed along with the rate at which each habitat would recover following impact (resilience). Sensitivity was scored based on a combination of the resistance of a habitat to damage and its subsequent rate of recovery. The assessments were based, wherever possible, on scientific literature, with expert judgement used to extrapolate results to habitat and gear combinations not directly examined in the published literature. The resulting sensitivity matrices were then subject to further peer review at a series of workshops. Following consensus on the habitat sensitivity, these data were combined with the most resolved sea‐floor habitat maps. These habitat sensitivity maps can help inform the development of site‐specific management plans, as well as having a place in spatial planning and aiding managers in developing dialogue with other stakeholders. A case study of their application is provided.

Maternal investment during pregnancy in wild meerkats - Stuart P. Sharp; Sinead English; Tim H. Clutton-Brock (Evolutionary Ecology, 2013)

Maximizing information from space data resources: a case for expanding integration across research disciplines - Nandu Goswami; Jerry J. Batzel; Gilles Clément; T. Peter Stein; Alan R. Hargens; M. Keith Sharp; Andrew P. Blaber; Peter G. Roma; Helmut G. Hinghofer-Szalkay (European Journal of Applied Physiology, 2013)

Plate-based diversity subset screening: an efficient paradigm for high throughput screening of a large screening file - Andrew S. Bell; Joseph Bradley; Jeremy R. Everett; Michelle Knight; Jens Loesel; John Mathias; David McLoughlin; James Mills; Robert E. Sharp; Christine Williams; Terence P. Wood (Molecular Diversity, 2013)

Variability and change in the Canadian cryosphere - C. Derksen; S. L. Smith; M. Sharp; L. Brown; S. Howell; L. Copland; D. R. Mueller; Y. Gauthier; C. G. Fletcher; A. Tivy; M. Bernier; J. Bourgeois; et al. (Climatic Change, 2012)
During the International Polar Year (IPY), comprehensive observational research programs were undertaken to increase our understanding of the Canadian polar cryosphere response to a changing climate. Cryospheric components considered were snow, permafrost, sea ice, freshwater ice, glaciers and ice shelves. Enhancement of conventional observing systems and retrieval algorithms for satellite measurements facilitated development of a snapshot of current cryospheric conditions, providing a baseline against which future change can be assessed. Key findings include: 1. surface air temperatures across the Canadian Arctic exhibit a warming trend in all seasons over the past 40 years. A consistent pan-cryospheric response to these warming temperatures is evident through the analysis of multi-decadal datasets; 2. in recent years (including the IPY period) a higher rate of change was observed compared to previous decades including warming permafrost, reduction in snow cover extent and duration, reduction in summer sea ice extent, increased mass loss from glaciers, and thinning and break-up of the remaining Canadian ice shelves. These changes illustrate both a reduction in the spatial extent and mass of the cryosphere and an increase in the temporal persistence of melt related parameters. The observed changes in the cryosphere have important implications for human activity including the close ties of northerners to the land, access to northern regions for natural resource development, and the integrity of northern infrastructure.

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Functional convergence of microbes associated with temperate marine sponges - M. Ribes; E. Jiménez; G. Yahel; P. López‐Sendino; B. Diez; R. Massana; J. H. Sharp; R. Coma (Environmental Microbiology, 2012)
Summary Most marine sponges establish a persistent association with a wide array of phylogenetically and physiologically diverse microbes. To date, the role of these symbiotic microbial communities in the metabolism and nutrient cycles of the sponge‐microbe consortium remains largely unknown. We identified and quantified the microbial communities associated with three common Mediterranean sponge species, Dysidea avara , Agelas oroides and Chondrosia reniformis ( Demospongiae ) that cohabitate coralligenous community. For each sponge we quantified the uptake and release of dissolved organic carbon (DOC) and nitrogen (DON), inorganic nitrogen and phosphate. Low microbial abundance and no evidence for DOC uptake or nitrification were found for D. avara . In contrast A. oroides and C. reniformis showed high microbial abundance (30% and 70% of their tissue occupied by microbes respectively) and both species exhibited high nitrification and high DOC and NH 4 + uptake. Surprisingly, these unique metabolic pathways were mediated in each sponge species by a different, and host specific, microbial community. The functional convergence of microbial consortia found in these two sympatric sponge species, suggest that these metabolic processes may be of special relevance to the success of the holobiont.

Gene Expression Profiling of Blood in Brain Arteriovenous Malformation Patients - Shantel M. Weinsheimer; Huichun Xu; Achal S. Achrol; Boryana Stamova; Charles E. McCulloch; Ludmila Pawlikowska; Yingfang Tian; Nerissa U. Ko; Michael T. Lawton; Gary K. Steinberg; Steven D. Chang; Glen Jickling; et al. (Translational Stroke Research, 2011)

Spatial movement optimization in Amazonian Eciton burchellii army ants - S. K. Willson; R. Sharp; I. P. Ramler; A. Sen (Insectes Sociaux, 2011)

Intra-uterine growth restriction is associated with increased apoptosis and altered expression of proteins in the p53 pathway in villous trophoblast - Alexander E. P. Heazell; Andrew N. Sharp; Philip N. Baker; Ian P. Crocker (Apoptosis, 2011)

Correlations Between Gene Expression and Mercury Levels in Blood of Boys With and Without Autism - Boryana Stamova; Peter G. Green; Yingfang Tian; Irva Hertz-Picciotto; Isaac N. Pessah; Robin Hansen; Xiaowei Yang; Jennifer Teng; Jeffrey P. Gregg; Paul Ashwood; Judy Van de Water; Frank R. Sharp (Neurotoxicity Research, 2011)

Correlations of Gene Expression with Blood Lead Levels in Children with Autism Compared to Typically Developing Controls - Yingfang Tian; Peter G. Green; Boryana Stamova; Irva Hertz-Picciotto; Isaac N. Pessah; Robin Hansen; Xiaowei Yang; Jeffrey P. Gregg; Paul Ashwood; Glen Jickling; Judy Van de Water; Frank R. Sharp (Neurotoxicity Research, 2011)

Impact of PSA testing and prostatic biopsy on cancer incidence and mortality: comparative study between the Republic of Ireland and Northern Ireland - A-E. Carsin; F. J. Drummond; A. Black; P. J. van Leeuwen; L. Sharp; L. J. Murray; D. Connolly; L. Egevad; M. Boniol; P. Autier; H. Comber; A. Gavin (Cancer Causes & Control, 2010)

Influence of age, sex, and aerobic capacity on forearm and skin blood flow and vascular conductance - Gary J. Hodges; Lisa Sharp; Richard E. Clements; David F. Goldspink; Keith P. George; Nigel T. Cable (European Journal of Applied Physiology, 2010)

The effect of 48 weeks of aerobic exercise training on cutaneous vasodilator function in post-menopausal females - Gary J. Hodges; Lisa Sharp; Claire Stephenson; Ashish Y. Patwala; Keith P. George; David F. Goldspink; N. Tim Cable (European Journal of Applied Physiology, 2010)

Identification of novel ω -gliadin gene in Aegilops tauschii using RFLP - M. Hassani; M. Naghavi; M. Shariflou; P. Sharp (Cereal Research Communications, 2009)

Late Holocene storm-trajectory changes inferred from the oxygen isotope composition of lake diatoms, south Alaska - Caleb J. Schiff; Darrell S. Kaufman; Alexander P. Wolfe; Justin Dodd; Zachary Sharp (Journal of Paleolimnology, 2009)

Identification and imaging of soil and soil-pile deformation in the presence of liquefaction - M. Zeghal; P. V. Kallou; C. Oskay; T. Abdoun; M. K. Sharp (Earthquake Engineering and Engineering Vibration, 2006)

Development and genetic mapping of sequence-tagged microsatellites (STMs) in bread wheat (Triticum aestivum L.) - M. J. Hayden; P. Stephenson; A. M. Logojan; D. Khatkar; C. Rogers; J. Elsden; R. M. D. Koebner; J. W. Snape; P. J. Sharp (Theoretical and Applied Genetics, 2006)

Aromatase inhibition abolishes courtship behaviours in the ring dove (Streptopelia risoria) and reduces androgen and progesterone receptors in the hypothalamus and anterior pituitary gland - M. D. C. Belle; P. J. Sharp; R. W. Lea (Molecular and Cellular Biochemistry, 2005)

Molecular structure of a novel y-type HMW glutenin subunit gene present in Triticum tauschii - M. E. Hassani; M. C. Gianibelli; M. R. Shariflou; P. J. Sharp (Euphytica, 2005)

A new approach to extending the wheat marker pool by anchored PCR amplification of compound SSRs - M. J. Hayden; P. Stephenson; A. M. Logojan; D. Khatkar; C. Rogers; R. M. D. Koebner; J. W. Snape; P. J. Sharp (Theoretical and Applied Genetics, 2004)

Dopamine agonists disrupt visual latent inhibition in normal males using a within-subject paradigm - Neal R. Swerdlow; Nora Stephany; Lindsay C. Wasserman; Jo Talledo; Richard Sharp; Pamela P. Auerbach (Psychopharmacology, 2003)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

Fasting differentially regulates expression of agouti-related peptide, pro-opiomelanocortin, prepro-orexin, and vasoactive intestinal polypeptide mRNAs in the hypothalamus of Japanese quail - D. Phillips-Singh; Q. Li; S. Takeuchi; T. Ohkubo; P. J. Sharp; T. Boswell (Cell and Tissue Research, 2003)

Genetic mapping of 66 new microsatellite (SSR) loci in bread wheat - P. Gupta; H. Balyan; K. Edwards; P. Isaac; V. Korzun; M. Röder; M.–F. Gautier; P. Joudrier; A. Schlatter; J. Dubcovsky; R. De la Pena; M. Khairallah; et al. (Theoretical and Applied Genetics, 2002)

Characterisation of Triticum vavilovii-derived stripe rust resistance using genetic, cytogenetic and molecular analyses and its marker-assisted selection - H. S. Bariana; G. N. Brown; N. U. Ahmed; S. Khatkar; R. L. Conner; C. R. Wellings; S. Haley; P. J. Sharp; A. Laroche (Theoretical and Applied Genetics, 2002)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Large angle convergent beam electron diffraction determinations of dislocation Burgers vectors in synthetic stishovite - P. Cordier; T. G. Sharp (Physics and Chemistry of Minerals, 1998)

Conserved TcR β chain usage for a single MHC class II-restricted heat shock protein peptide - Gail E. Hawes; Linda Struyk; Helen Beacock-Sharp; Judy Henwood; J. S. Hill Gaston; P. J. van den Elsen (Immunogenetics, 1998)

A study of females with deletions of the short arm of the X chromosome - Rowena S. James; Brian Coppin; Paola Dalton; Nicholas R. Dennis; Caroline Mitchell; Andrew J. Sharp; David H. Skuse; N. Simon Thomas; P. A. Jacobs (Human Genetics, 1998)

The effect of infusion of hypertonic saline on glomerular filtration rate and arginine vasotocin, prolactin and aldosterone in the domestic chicken - A. M. Leary; J. R. Roberts; P. J. Sharp (Journal of Comparative Physiology B, 1998)

Electron-beam induced amorphization of stishovite: Silicon-coordination change observed using Si K -edge extended electron energy-loss fine structure - P. A. van Aken; T. G. Sharp; F. Seifert (Physics and Chemistry of Minerals, 1998)

Gender comparison of peak oxygen uptake: repetitive box lifting versus treadmill running - Bradley C. Nindl; Marilyn A. Sharp; Robert P. Mello; Valerie J. Rice; Michelle M. Murphy; John F. Patton (European Journal of Applied Physiology, 1997)

Characterisation of Fusarium Avenaceum Subspecies Avenaceum, Nurragi and Aywerte - F. H. L. Benyon; L. W. Burgess; P. J. Sharp (Cereal Research Communications, 1997)

Increase of 5-HT 7 (serotonin-7) and 5-HT 1A (serotonin-1A) receptor mRNA expression in rat hippocampus after adrenalectomy - S. Le Corre; T. Sharp; A. H. Young; P. J. Harrison (Psychopharmacology, 1997)